Investment in Innovation and its Influence on Net Sales: An Analysis Based on PINTEC Data - Tatielle Menolli Longhini; Joyce Mariella Medeiros Cavalcanti; Sergio Louro Borges; Bruno Pérez Ferreira (BBR: Brazilian Business Review)
The aim of this research is to analyze the influence of innovation investments on net sales from major national sectors. The data was collected from the free access to the Technological Innovation Research (PINTEC) database. To proceed the analysis, we collected the PINTEC data from the years 2000, 2003, 2005, 2008 and 2011, consolidating them in a specific way. The analysis were developed through regressions of panel data with fixed effects, according to Hausman test, and the definition of large scale sectors was based on the median of net sales. The results suggest that, on average, for the large scale sectors the acquisition of machinery & equipment and industrial projects & other technical improvements are statistically relevant variables to increase the net sales.